Frecuencia de riego con biofertilizante foliar en las características agronómicas y el rendimiento en Coriandrum sativum L. culantro. Loreto - Vela Gomez, Paolo (2024)
The objective of this research was to evaluate the effect of different frequencies of foliar biofertilizer irrigation on the agronomic development and productivity of Coriandrum sativum L. Grand Rapid variety cilantro. Employing a controlled experimental design (CRBD) with 5 replications, plants were irrigated with foliar biofertilizer at intervals of three, six, and nine days, with an unwatered control. Variables such as plant height, root length, number of branches and leaves, and total plant weight were measured. The results demonstrated that the irrigation frequency did not have a significant effect on plant height, root length, number of branches and leaves, indicating that these aspects of vegetative development are not significantly affected by foliar biofertilizer application within the evaluated ranges. However, the total plant weight showed significant differences, with the treatments every three days being superior to the others in terms of weight, with a p-value < 0.01 and a low coefficient of variation (10.91%), suggesting a positive effect of increased application frequency on total crop biomass. This research provides evidence of the effectiveness of foliar biofertilizers in increasing cilantro productivity by enhancing total biomass, highlighting the importance of adjusting irrigation practices to optimize results. Keywords: Biomass, Productivity, Experimental Design, Biofertilizer foliar.